3D finite element analysis of a wood dowel in bending perpendicular to the grain / Haslin Idayu Amaruddin and Rohana Hassan - Amaruddin, Haslin Idayu; Hassan, Rohana (Universiti Teknologi MARA, Pahang, 2022)
This paper simulated the bending behavior of a wood dowel in a three-point bending test using the Finite Element Method (FEM) in ANSYS Workbench. Most researchers performed a three-point bending test to measure the flexural strength parallel to the wood grain. In this paper, the analysis is carried out perpendicular to the grain direction. The three-point bending test provides the mechanical properties of the wood, such as the modulus of elasticity and the modulus of rupture. These properties are important to define orthotropic wood material in finite element modeling. The aim is to determine the modulus of elasticity of the wood dowel perpendicular to the grain. The process overview of modeling wood elements in ANSYS is also presented. The results from the FEM were then compared with the experimental results from laboratory tests. In this work a good agreement between FEM and experimental results was obtained. The modulus of elasticity obtained was relatively very small in the perpendicular direction compared to the value in the parallel direction.